Penafsiran Hadits Sufistik (Telaah Pemikiran Syekh Nawawi Al Bantani Dalam Kitab Qomi’tughyan) - Abdul Rohim; Dadah Sa’adah (Yayasan Cendekia Gagayunan Indonesia, 2024)
This study aims to examine the interpretation of Sheikh Nawawi al-Bantani on the hadiths of the branch of faith contained in the book of Qami'tughyan. This research uses a descriptive qualitative method with a literature study approach to collect and analyze relevant data. The analysis method used is content analysis, which aims to explore the meaning and explanation contained in the book. The results showed that Sheikh Nawawi's explanation on points related to Sufism in the book of Qami'tughyan did not contradict the teachings of naqli and aqli. His in-depth interpretation of the aspects of Sufism makes a significant contribution in clarifying the meaning of the Prophet's hadith, as well as strengthening the understanding of his words. This study concludes that Sheikh Nawawi's interpretation is instrumental in enriching Muslims' understanding of hadiths related to aspects of Sufism and faith.